Coming out within: Qualitative inquiry in psychology - Bradbury, Jill (PINS-Psychology in Society, 2025)
On the eve of the 30th birthday of PINS, celebrating its coming-of-age as the key journal for publishing critical psychological work in South Africa, I had the delight of participating in the “coming-out party” for a new-kid-on-the-block in New York. The event was the official launch of the newly formed Society for Qualitative Inquiry in Psychology (SQIP) and its associated journal, Qualitative Psychology and, like in all the best parties, the talk was both full of frivolous fun, and serious, interesting ideas.